2009
DOI: 10.1557/jmr.2009.0010
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical behavior of ultrafine-grained Ni processed by different powder metallurgy methods

Abstract: Ultrafine-grained samples were produced from a Ni nanopowder by hot isostatic pressing (HIP) and spark plasma sintering (SPS). The microstructure and mechanical behavior of the two specimens were compared. The grain coarsening observed during the SPS procedure was moderated due to a reduced temperature and time of consolidation compared with HIP processing. The smaller grain-size and higher nickel-oxide content in the SPS-processed sample resulted in a higher yield strength. Compression experiments showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
5
32
0
Order By: Relevance
“…[4,10] The UFG grains in bi-modal materials are known to promote a high strength by limiting dislocation movement, whereas the micron-sized grains occupy a larger proportion of the microstructure on a volumetric basis, thus increasing their effect on the behavior of the aggregate, such as ductility, by suppressing crack growth and facilitating plastic deformation. [4] Although a large amount of published work has qualitatively verified that the introduction of multi-scale grain structures can indeed improve the poor ductility of UFG materials, [11][12][13][14][15][16][17][18][19][20][21][22] this approach represents in fact, a compromise strategy: i.e., to achieve ductility by sacrificing strength. The question is what is the extent of such a compromise?…”
mentioning
confidence: 99%
“…[4,10] The UFG grains in bi-modal materials are known to promote a high strength by limiting dislocation movement, whereas the micron-sized grains occupy a larger proportion of the microstructure on a volumetric basis, thus increasing their effect on the behavior of the aggregate, such as ductility, by suppressing crack growth and facilitating plastic deformation. [4] Although a large amount of published work has qualitatively verified that the introduction of multi-scale grain structures can indeed improve the poor ductility of UFG materials, [11][12][13][14][15][16][17][18][19][20][21][22] this approach represents in fact, a compromise strategy: i.e., to achieve ductility by sacrificing strength. The question is what is the extent of such a compromise?…”
mentioning
confidence: 99%
“…X-ray diraction and energy-ltered TEM investigations revealed that there is a native crystalline NiO layer on the surface of Ni powder particles [38]. In the sintered materials this phase appears in the form of dispersoids in the Ni matrix.…”
Section: Methodsmentioning
confidence: 99%
“…In the following, the inuence of the initial powder particle size, the time and temperature of sintering and the atmosphere used in powder processing on the microstructure and plastic properties will be illustrated on Ni. One sample was produced from a nanopowder with the average particle size of about 100 nm by hot-isostatic pressing (HIP) [38]. Before HIP, the glass containing the powder was broken in a glove-box and subsequently encap- Finally, in order to study the eect of the initial powder particle size on the microstructure, a fourth sample was consolidated from a Ni powder with the average particle size of 50 nm by SPS under the same conditions as for the previous specimen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter powder had previously been internally characterized in a separate earlier work, including the determination of its chemical composition by inductively coupled plasma spectroscopy [6].…”
Section: Methodsmentioning
confidence: 99%